Pengaruh Model Pembelajaran Kontekstual Bahasa Indonesia dalam Menulis Resensi Berbasis di Kelas Vll SMP Negeri 1 Batang Kuis - Nur Suaimah; Rina Devianty; Edi Saputra (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to determine the influence of the Indonesian language contextual learning model in writing e-book based reviews in class VII of SMP Negeri 1 Batang Kuis and to obtain an overview of the influence of the Indonesian language contextual learning model in writing e-book based reviews in class VII of SMP Negeri 1 Batang Kuis This research was carried out on May 29 2024 at SMP Negeri 1 Batang Kuis. The approach taken in this research is quantitative. The sample technique is taken 20% of the total population. The research instrument used was a questionnaire. The results found in this research are that there is a significant influence between the Indonesian contextual learning model in writing e-book based reviews in class VII SMP Negeri 1 Batang Kuis. The results of the research show that if you look at the accumulated data in table 21, there are respondents in the strongly agree category with a score of 412, respondents in the agree category with a score of 579, respondents in the disagree category with a score of 196 and respondents in the disagree category with a score of 11 so that it can be drawn. The conclusion is that students generally admit that they have the ability to write e-book based reviews using the contextual learning model.